1997
DOI: 10.1111/j.1365-246x.1997.tb00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeosecular variation in Central Mexico over the last 30 000 years: the record from lavas

Abstract: S U M M A R Y 13 lava flows of known age (ages from I4C dating), which have been erupted in the last 30000 years, have been studied to determine the palaeosecular variation of the geomagnetic field in Central Mexico. Samples were taken from two different monogenetic volcanic fields: the Michoacan-Guanajuato volcanic field (six sites) and the Chichinautzin Formation (seven sites), both part of the Transmexican Volcanic Belt. The lavas were studied in detail using rock magnetic methods (magnetic susceptibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 51 publications
6
34
0
Order By: Relevance
“…Previous PI results of Xitle lava flows Gonzalez et al, 1997;Nagata et al, 1965;Morales-Contreras, 1995;Morales et al, 2003;and UrrutiaFucugauchi, 1996) found very similar mean values to our mean PI estimate (Fig. 11, Table 4).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous PI results of Xitle lava flows Gonzalez et al, 1997;Nagata et al, 1965;Morales-Contreras, 1995;Morales et al, 2003;and UrrutiaFucugauchi, 1996) found very similar mean values to our mean PI estimate (Fig. 11, Table 4).…”
Section: Discussionsupporting
confidence: 76%
“…(5) Earlier PI studies of the Xitle lava flow disclose intensely varying mean paleointensities (Table 4), ranging from 58 to 77 μT Gonzalez et al, 1997;Nagata et al, 1965;MoralesContreras, 1995;Morales et al, 2003;UrrutiaFucugauchi, 1996). All of these studies were performed on single or several lava flows exposed at dis-tinct places over the flanks of the volcano.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, some thermal alteration from this heating can be corrected for [29,30]. In practice, results generally tend to agree with those of the Thellier method, but in several cases have been reported to show more scatter [31,32].…”
Section: Experimental Uncertaintiessupporting
confidence: 60%
“…These directions, are practically indistinguishable from the expected Plio-Quaternary paleodirections, as derived from the reference poles for the North American polar wander curve (Besse and Courtillot, 2002) and is in agreement with previous studies and compiled data from the MGVF (Tables 2 and 3, Fig. 7) considering all previously reported studies (Gonzalez at al., 1997;Bohnel and Molina, 2002;Panfil, 1999;Michalk et al, 2010;Maciel Peña et al, 2009). This suggests that no major tectonic deformation occurred in the studied area since the Late Pliocene to the present.…”
Section: Main Results and Discussionsupporting
confidence: 91%
“…Table 2. Flow-mean paleodirections of characteristic remanence, location and available isotopic age determinations (1 - Gonzalez et al, 1997, 2 -Bohnel and Molina, 2002, 3 -Panfil, 1999, 4 -Michalk et al, 2010, 5 -Maciel Peña et al, 2009 The mean paleodirection obtained in this study is inclination I = 28.8°, declination D = 354.9°, Fisherian parameters k = 28,  95 = 7.3°, N = 15, which corresponds ( Fig. 6) to the mean paleomagnetic pole position P lat = 83.9°, P long = 321.6°, K = 34, A 95 = 6.6°.…”
Section: Main Results and Discussionmentioning
confidence: 99%